Detail specification for solder-sealed quartz crystal units for oscillator applications. AA, CX, BF and BC/1 enclosures, 17 to 75 MHz frequency range. Third overtone thickness-shear mode, AT-cut, for operation over wide temperature ranges (non- temperature controlled). Full assessment level. (15th October 1977) - British Standards Institution,
No abstract available